2017
DOI: 10.1177/0145445517725048
|View full text |Cite
|
Sign up to set email alerts
|

The Evidence Base for Interventions Targeting Individuals With Work-Related PTSD: A Systematic Review and Recommendations

Abstract: The purpose of this study was to summarize the evidence base for interventions targeting individuals with work-related posttraumatic stress disorder (PTSD), to make recommendations for clinicians and administrative decision makers involved in their rehabilitation, and to guide future research in this area. Particular attention was given to studies that were conducted in naturalistic clinical settings or in a workers' compensation claim context. Electronic searches of Cochrane Central Register of Controlled Tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 62 publications
(158 reference statements)
1
13
0
Order By: Relevance
“…The authors of three reviews (Stergiopoulos et al, 2011; Chen et al, 2014; Thomaes et al, 2014) had reported their search strategies in such a manner that we could answer the critical appraisal question: “Do you think all the important, relevant studies were included?” with “Yes”. For four reviews (Zantvoord et al, 2013; Cusack et al, 2016; Swan et al, 2017; Torchalla and Strehlau, 2017), it was unclear whether the reported search strategy had found all important, relevant studies; for two of these, Cusack et al (2016) and Zantvoord et al (2013), we were unable to access the full search strategy. We answered the question with “No” for thirteen of the reviews (Lapp et al, 2010; Goodson et al, 2011; Haugen et al, 2012; Ho and Lee, 2012; Mello et al, 2013; Watts et al, 2013; Ehring et al, 2014; Jong et al, 2014; Chen et al, 2015; Haagen et al, 2015; Erford et al, 2016; Lenz et al, 2017; Tribe et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The authors of three reviews (Stergiopoulos et al, 2011; Chen et al, 2014; Thomaes et al, 2014) had reported their search strategies in such a manner that we could answer the critical appraisal question: “Do you think all the important, relevant studies were included?” with “Yes”. For four reviews (Zantvoord et al, 2013; Cusack et al, 2016; Swan et al, 2017; Torchalla and Strehlau, 2017), it was unclear whether the reported search strategy had found all important, relevant studies; for two of these, Cusack et al (2016) and Zantvoord et al (2013), we were unable to access the full search strategy. We answered the question with “No” for thirteen of the reviews (Lapp et al, 2010; Goodson et al, 2011; Haugen et al, 2012; Ho and Lee, 2012; Mello et al, 2013; Watts et al, 2013; Ehring et al, 2014; Jong et al, 2014; Chen et al, 2015; Haagen et al, 2015; Erford et al, 2016; Lenz et al, 2017; Tribe et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…However, the program did not include a return-to-work component. Existing treatment manuals usually lack information on how to address return to work, and the few studies that did modify therapy protocols to facilitate this were conducted with workers who had experienced a single trauma, most notably workers with industrial injuries (see Torchalla & Strehlau 2018 for an overview). Occupational therapists are trained in functional capacity evaluation and thus are well qualified to address work-related psychological impairments and return to work.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, expectations are related to both symptom reduction and resumption of work. However, research reporting return-to-work outcomes of interventions for individuals with work-related PTSD has remained scant (Torchalla & Strehlau, 2018 ). In addition, despite the strong evidence for the effectiveness of exposure-based psychotherapies, they remain underutilized by community-based clinicians (Pittig et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…One of the explanations offered for this phenomenon is that those who seek compensation may be afraid of not receiving recognition and compensation if they report significant improvements in their PTSD symptoms (Walter et al, 2014). Furthermore, many may struggle with returning to work after being treated for profession-related PTSD (Torchalla & Strehlau, 2018), for example because of residual symptoms such as concentration problems (Smid et al, 2018) or fear of stigmatization (Haugen, et al, 2017)-which might influence symptom reporting. Finally, this finding could be related to the larger occupational context of police officers in the Netherlands.…”
Section: Treatment Outcome Predictorsmentioning
confidence: 99%